Agricultural R&D: Is Africa investing enough? - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2014)
Given the goals of economic growth and poverty reduction, as well as the challenges of rapid population growth, climate change, and food price volatility, Africa south of the Sahara must invest in research and development (R&D) to boost agricultural productivity. This chapter provides a data-driven analysis of the region’s recent progress in investing in financial resources and human resource capacity related to agricultural R&D.